The use of water hyacinth mulch and sewage sludge in gold tailings to improve soil fertility and stability - Wanenge, Macdonald. T (My University, 2013)
Gold tailings contained in Tailing Storage Facilities (TSFs) contain pyrite which on exposure to air and water becomes a source of acid mine drainage (AMD). AMD has high salinity, elevated levels of heavy metals and low pH, which presents serious threats to surface and groundwater systems. These characteristics in tailings present a hostile environment for plant establishment and growth (Witkowski and Weiersbye 1998a). Therefore, it was hypothesized that organic mulch sourced from sewage sludge and water hyacinth could improve tailings fertility on TSFs in the Highveld gold mines of South Africa. The aim of this study was to develop a greenhouse study to understand how four indigenous plants (Asparagus laricinus Burch. (Asparagaceae), Eragrostis curvula (Schrad.) Nees. (Poaceae), Hyparrhenia hirta (L.) Stapf (Poaceae) and Sutherlandia frutescens (L.) R.Br. (Fabaceae) naturally colonizing the Highveld gold TSFs would survive, grow and accumulate metals from tailings amended using different percentages of water hyacinth and/or sewage sludge, and the susceptibility of the amended tailings to metal leaching. Tailings amended with WH: SS-1.0% proved to be the overall best amendment from the 19 treatments based on the variable tested (e.g. plant growth, plant metal uptake and metal leaching). Amending gold tailings with water hyacinth and/or sewage sludge improved seedling survival, plant survival and growth as compared to non-amended tailings. Tailings amended with dry water hyacinth (WH) created the most favourable plant growing conditions especially at 0.5% of amendment, while those amended only with sewage sludge (SS) presented the most challenging plant growth conditions for all four study species. Amending tailings with water hyacinth and/or sewage sludge showed no significant difference in tailings fertility. However, C (%) and total N decrease significantly after plant growth in all treatments. Hyparrhenia plants grown in tailings amended with WH: SS-1.0% accumulated significantly higher concentrations of Al, Cr, Ni and Zn, while those growing in tailings amended with WH-0.5% accumulated significantly lower concentration of Al, Co, Cr, Fe and Zn as compared to other treatments. Tailings amended with WH-1.0% leached significantly higher concentrations of Mn, while those amended with WH: SS-0.5% and WL-2.0% leached significantly higher concentrations of S as compared to other treatments. All four species accumulated significantly higher concentrations of Al, Co, Cr, Cu, Fe and Ni in the roots than the shoots, except for A. laricinus which accumulated significantly higher concentrations of S, Co, Cr, Mn, Ni and Zn in the shoots than the roots. Sutherlandia frutescens retained all the elements tested in its root biomass. Future field studies in the use of water hyacinth and sewage sludge as organic tailings amendments will be required to get a better understanding of these two potential tailings amendment treatment.
Keywords: Soil fertility - South Africa.; Sustainable agriculture.; Water hyacinth.; Sewage sludge as fertilizer.